Juego dramático y su contribución en el desarrollo de las habilidades cognitivas en los estudiantes de educación inicial de la Unidad Educativa Guillermo Baquerizo - Valero Chang, Nieve Alexandra (2018)
In the present work we find several chapters dedicated to demonstrate that the application of dramatic play as an effective teaching technique to children who are in the initial education stage, has great importance for the significant learning that can be generated in the students, it is also a way to make a class fun and easy to execute. The Guillermo Baquerizo Educational Unit presented a lack of interest on the part of teachers in the implementation and use of space for dramatic play in the teaching-learning process, since it seems that the game is not considered as a methodological resource or strategy for teaching, making it difficult that children achieve learning experiences. In a referential framework we can discover that, in the dramatic game, different forms of expression converge: oral expression, gestural, sound, musical, plastic, etc., can be manifested in the different moments of the activity. With this, dramatic play becomes an important element of educational globalization, representing a nexus between the different expressive modalities. In the conceptual framework we discover the following; The concept of "cognitive abilities" comes from the field of cognitive psychology. These are operations of thought by means of which the subject can appropriate the contents and the process he used for it. These have three axes: The attention, through this and a constant exercise, will favor the development of skills such as: observation, classification, interpretation, etc. The responsibility of adapting a space destined for the dramatic game is of the teachers, it also depends on them the learning that the children can acquire through the game, since they are the ones in charge of guiding them and accompanying them to the children in the interaction exploration and dramatization and to understand the meaning of what they observe in each of the representations or dramatizations